The politics of promoting social cash transfers in Uganda: The potential and pitfalls of "thinking and working politically". (11th March 2020) - Hickey, Sam; Bukenya, Badru
Abstract: Motivation: Social cash transfer programmes (SCTs) have spread rapidly in sub‐Saharan Africa during the last decade. However, there is little consensus on how this has happened, particularly in terms of the relative roles of international development agencies and national‐level political factors. Uganda is one of several countries to have adopted cash transfers since 2010 and can offer important insights into how this process has unfolded. Purpose: Theoretical advances suggest that transnational policy transfer is most effective when international actors are able to align their proposals with domestic political dynamics. This article examines how the adoption of a "thinking and working politically" approach enabled donors to shape the uptake of SCTs in Uganda. It investigates what happens when a "going with the grain" approach is deployed in a context where domestic political dynamics are moving further away from the progressive forms of politics that proponents of social protection in Africa have often heralded. Approach and methods: The article is based on an in‐depth qualitative case study of the promotion of SCTs in Uganda. Over 35 key informant interviews were undertaken with all key stakeholders, particularly between 2014–2016 after the government of Uganda announced a scaling‐up of SCTs. The triangulation of these accounts within a rigorous process‐tracing methodology enables us to link key turning points in this process to donor strategies and Uganda's changing political settlement. Findings: Donor efforts to promote SCTs in Uganda prospered when a shift was made from a technocratic to a more politically informed approach in the late 2000s. By employing strategies from the new "thinking and working politically" agenda, an alignment was eventually achieved between SCTs and Uganda's shifting political settlement, including the president's increased vulnerability to popular pressures and the commercialization of patron–client politics. However, cash transfers have been adopted primarily as a form of clientelism rather than as a strategy for promoting either significant levels of poverty reduction or an improved social contract. Policy implications: The findings suggest that the "thinking and working politically" agenda carries significant risks when applied in contexts such as Uganda, where the political conditions for development are deteriorating.